Perhatian Orang Tua terhadap Pembiasaan Ibadah Shalat Anak di Kelurahan Bungus Barat Kecamatan Bungus Teluk Kabung - Sherly Tria Amanda; Wirdati Wirdati (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
This research is motivated because there are still many children who do not pray so that it becomes a significant obstacle for parents in educating and raising children. The purpose of this study was to find out how parents pay attention to the habit of praying for children in Bungus Barat Village. This study uses a qualitative method with a case study approach. Data collection techniques used are observation, interviews, and documentation. Data analysis with data reduction, data presentation and conclusion drawing. The researcher used source triangulation to verify the validity of the data. The results of this study indicate that parents who give physical attention can be seen from parents who provide children's prayer equipment. in maintaining health, not everyone can pay attention to the health of their children because they are busy working, from parents who pay attention to their children's health, it can be seen from the habits of parents who teach children to live healthy. To give gifts and punishments, judging from the differences in opinion of parents, there are some parents who give gifts and punishments to children, some do not. While parents who pay attention psychologically can be seen from some parents who do not pay attention to children in carrying out prayers, because they are busy at work and do not understand religion so they cannot fully provide guidance, advice and supervision to children to be able to carry out prayers.